Isolation and detection of biosurfactant producing bacteria from Palm Kernal Cake (PKC) - Vello, Sumathy; Jamal, Parveen; Salleh, Md. Noor; Alam, Md. Zahangir; Jami, Mohammed Saedi (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
The present research study was aimed to isolate and detect for biosurfactant producing microorganisms from Palm Kernal Cake (PKC). Seven bacteria were isolated from PKC and labelled as SV1, SV2, SV3, SV4, SV5, SV6 and SV7. It was found that almost all the bacteria are potential biosurfactant producers as they were positive for most of the detection method. Two bacteria, SV1 and SV6 tested positive for hemolysis activity. Five bacterial strains gave positive results for drop collapse assay test. Good activity was observed in Emulsification Index and oil displacement test. Surface tension measurements were moderate for all the isolates with the best surface tension of 43.08 mN/m for SV1.